Endoscopic and Pathologic Resolution of Chronic Nonsteroidal Anti-Inflammatory Drug-Induced Diaphragm-Like Colonic Strictures and Ulceration - Behdod Poushanchi; Hiren Vallabh; Justin Kupec (Case Reports in Gastrointestinal Medicine)
The chronic use of nonsteroidal anti-inflammatory drugs (NSAIDs) has steadily increased and, as a result, adverse effects have become more common. Isolated case reports have documented diaphragm-like colonic strictures and ulceration as the result of NSAID use. We report a unique case of this rare side effect with documented endoscopic and histologic healing of multiple proximal diaphragm-like colonic strictures and ulceration months after simple discontinuation of NSAID therapy.